Spelling writing error analysis in nonfiction essay of elementary students - Ali Mustadi; Miftakhul Amalia (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2020)
Spelling writing error often occurs in an essay. The spelling error is found in nonfiction essays of the V grade students. This research purpose is to describe the error in spelling writing in nonfiction essays of V grade students in SD Negeri 1 Kadipiro, Kasihan Bantul. The research is a content analysis research using a qualitative approach. The data source of this research is Indonesian nonfiction essays. Data collecting technique used was reading and by note-taking. The instrument of the research is the mechanical analysis sheet. Validity used in this research is semantic validity. Reliability of this research is stability and reproducibility. Analysis unit in this research covers letters usage, writings words, use of punctuation, and uptake words writings element. The data analysis technique used consists of data collection, sample determination, recording/noting, reduction, and drawing a conclusion. The research finding shows that there are writing errors in student’s nonfiction essay, such as letter usage (54,47%), word writing errors (25%), error in using punctuation (18,16%), and error in writing uptake words (2,37%). Factors that cause errors in writing include limited time in learning to write, lack of mastery in spelling rules, and lack of accuracy in writing.